Selective radiolabelling with 68Ga under mild conditions: a route towards a porphyrin PET/PDT theranostic agent. Issue 57 (29th June 2018) - Yap, Steven Y.; Price, Thomas W.; Savoie, Huguette; Boyle, Ross W.; Stasiuk, Graeme J.
Abstract : A theranostic porphyrin conjugate for use as a positron emission tomography (PET) radiotracer and as a photosensitiser for photodynamic therapy (PDT) has been synthesised. This conjugate can be radiolabelled with 68Ga at pH 7.4 at room temperature with an RCY of 80%. Abstract : A theranostic conjugate for use as a positron emission tomography (PET) radiotracer and as a photosensitiser for photodynamic therapy (PDT) has been synthesised. A water-soluble porphyrin was coupled with the bifunctional chelate, H4 Dpaa.ga. This conjugate is capable of rapid 68 Ga complexation under physiological conditions; with 93% and 80% radiochemical yields achieved, at pH 4.5 and pH 7.4 respectively, in 15 min at 25 °C. Photocytotoxicity was evaluated on HT-29 cells and showed the conjugate was capable of >50% cell death at 50 μM upon irradiation with light, while causing minimal toxicity in the absence of light (>95% cell survival).